Revisiting AgCrSe2 as a promising thermoelectric material. Issue 34 (15th August 2016) - Wu, Di; Huang, Sizhao; Feng, Dan; Li, Bing; Chen, Yuexing; Zhang, Jian; He, Jiaqing
Abstract : Superionic AgCrSe2 shows a "non-superionic" specific heat and a reversible decomposition process above 723 K. Abstract : We revisited and investigated a layer-structured thermoelectric material AgCrSe2, which has an extremely low thermal conductivity. After using both differential scanning calorimetry and a comparative laser flash method, we realized that the specific heat of this material, the main contributor to the reported low thermal conductivity, is unlikely to be way below the Dulong–Petit limit as revealed in the literature. Besides, our in situ X-ray diffraction pattern up to 873 K indicated the instability of AgCrSe2 over 723 K, where it begins to decompose into Cr2 Se3 and Ag2 Se. This unexpected decomposition phenomenon resulted in the gradual increment of specific heat and thermal diffusivity, hence the deterioration of the overall thermoelectric performance. We deliberately introduced Ag and Cr vacancies into the lattice for carrier concentration optimization and could achieve an optimal figure of merit of ZT ∼ 0.5 at 723 K in the nominal composition Ag0.96 CrSe2 in the direction perpendicular to the sintering press. Our findings suggest that more thorough investigations are necessary to ensure that AgCrSe2 is a promising thermoelectric material.